Implementation Of Physical Education Sports And Health Learning: Case Study at Fathul Mubin Elementary School, Bandung Regency - Purnama, Fikri Novandi; Surya, Candra Mochamad; Hendar, Hendar (International Journal of Science Education and Technology Management, 2024)
The background of this study is the absence of professional Physical Education, Sports and Health Teachers at MI Madrasah Ibtidaiyah Fathul Mubin, Bandung Regency. This study was conducted with the aim of finding out how well the implementation of physical education, sports and health learning is at Madrasah Ibtidaiyah Fathul Mubin, Bandung Regency. This study is a type of qualitative descriptive research, which describes how the implementation of physical education, sports and health is at Madrasah Ibtidaiyah Fathul Mubin, Bandung Regency. The subjects in this study were 6 teachers and 1 principal. The data collection techniques used in this study were observation, interviews and documentation. The data analysis techniques used in this study were data reduction and data display techniques. The results of the study showed that the implementation of physical education, sports and health at Madrasah Ibtidaiyah Fathul Mubin, Bandung Regency in terms of preparation was quite good, while in the implementation and evaluation stages it was still relatively poor. In addition, the role of class teachers who also serve as Physical Education, Sports and Health Teachers has not been able to show good performance in its implementation